Life Cycle Assessment in practice - Exploring the work surrounding the Nouryon eco-footprint - Algestrand, Gustav (My University, 2021)
Life Cycle Assessment (LCA) is an emergent tool for assessing sustainability in industry by providing environmental performance data of products. While there is a large variety of standards available, as well as scientific knowledge of how to perform LCA calculations, there is little such information on how to structure the work and organization surrounding LCA, so called Life Cycle Management (LCM) or life cycle practice, i.e., how to manage data, what actors to involve, in what format to communicate the results etc. The aim of this work has been to provide insights in how LCA is practiced in industry, focusing on the company Nouryon, which has a long history of driving the sustainability agenda in the chemical industry by using LCA and what they refer to as Eco-footprints of products. First, the sustainability organization was mapped, in order to determine the prerequisites for practicing LCA at the company and the carrying out of eco-footprints, but also to acknowledge barriers and areas of improvements. Second, a comparison was made with external standards for environmental market communication, primarily Environmental product declarations (EPD) and the Product environmental footprint (PEF), in order to identify and evaluate aspects important to address in the Nouryon ecofootprint methodology. Lastly, suggestions on how to approach the identified barriers and areas of improvement as well as incorporating relevant aspects were presented. The outcome of this work may therefore act as a basis for further, more detailed measures for standardizing the internal work surrounding eco-footprints at Nouryon but may also provide valuable insights on life cycle practice to the LCA community as a whole.
Keywords: Life Cycle Assessment; LCA; Life Cycle Practice; Life Cycle Management; LCM; Product Environmental Footprint; PEF; Environmental Product Declaration; EPD